Comparison of Control Strategies for Aircraft Bleed-Air Systems. Issue 1 (July 2017) - Pollok, Alexander; Casella, Francesco
Abstract: Bleed-air systems in passenger aircraft are often prone to limit cycle oscillations. Tuning of such systems makes additional flight-tests necessary, generating large expenses. In this paper, several control approaches to improve the performance of bleed-air systems are compared. These approaches combine a base-controller with stiction-compensation techniques. The different approaches are implemented, optimized and evaluated using a high-fidelity bleed-air system model, described in the equation-based modelling language Modelica. Results indicate that interaction between different valves should be reduced as much as possible. If a suitable base control approach is chosen, the influence of a superimposed stiction compensation technique seems to be small.